2019
DOI: 10.1590/1413-785220192705219143
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients With Sarcoma After Conservative Surgery or Amputation of Limbs

Abstract: Objective:To conduct an integrative review on quality of life (QOL) of patients with sarcoma who underwent conservative surgery or limb amputation.Methods:We conducted a six-step integrative review by searching the databases LILACS, SciELO, PePSIC, Embase, and PubMed, using the descriptors: “Quality of life”, “Bone cancer”, “Sarcoma”, “Limb Salvage,” and “Amputation.” Ten studies were selected according to: database, type of study, methods, researcher's profession, sex, histological type, title, country/region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In the perception of quality of life, only constipation was higher in amputees than in those undergoing conservative surgery. According to data by Silva et al, ( 10 there are no publications so far in patients with sarcoma, which may justify such findings. Wickham 24 in a review study concluded that constipation is common in cancer patients and its frequency is high in those with advanced disease and using opiate drugs to treat pain.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In the perception of quality of life, only constipation was higher in amputees than in those undergoing conservative surgery. According to data by Silva et al, ( 10 there are no publications so far in patients with sarcoma, which may justify such findings. Wickham 24 in a review study concluded that constipation is common in cancer patients and its frequency is high in those with advanced disease and using opiate drugs to treat pain.…”
Section: Discussionmentioning
confidence: 90%
“…The scientific production on quality of life of patients with sarcoma is small. Silva et al ( 10 ) in an integrative review on quality of life in sarcoma patients undergoing different types of surgery (amputation versus conservative) found only ten studies in the main databases (LILACS, SciELO, Pepsic, EMBASE and PubMed). No Brazilian studies had been published.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional impairment in a postoperative state occurs according to the degree of resected tissue. Thus, appropriate rehabilitation is required to achieve good activities of daily living (ADL) and quality of life outcomes [2,3].…”
Section: Introductionmentioning
confidence: 99%